Large-scale refactoring challenges and coordination in open source software development. (7th October 2020) - Moon, Eunyoung; Howison, James
Increasingly complicated software makes it difficult to attract or maintain open source software (OSS) contributors. Faced with such challenges of increasingly complicated software design, large-scale refactoring that radically restructures the architecture of the software can be one of the solutions. In this study, we investigate and illustrate how OSS contributors accomplish large-scale refactoring in OSS development in which there is no significant corporate participation. In our observations, as the costs of coordination requirements rise, OSS contributors increase coordination capability to manage dependencies among multiple sources during the large-scale refactoring periods. Our findings suggest that OSS contributors episodically use traditional coordination mechanisms during the large-scale refactoring periods. Our study provides actionable insights into how OSS contributors make joint action that cannot be achieved by individuals working independently and use the provision of rewards in order to achieve a shared, explicit goal of large-scale refactoring.